“THE INFLUENCE OF PROFITABILITY ON INTERNET FINANCIAL REPORTING DISCLOSURE” - Almira Cahya Kartika (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The study aims to examine the effect of profitability to the level of internet financial report disclosure by Indonesian listed companies. The profitability is measured by earnings per share, net profit margin, return on equity, pay-out ratio and addition control variables as firm size and return on asset. The study modifies and uses the disclosure index of Aly, et al. (2010). The sample in this study uses purposive and cluster sampling of 214 companies from all sectors of listed companies in Indonesian Stock Exchange for the year of 2015. Multiple regression analysis is used to examine the influence of profitability towards internet financial reporting. It is found that the profitability ratios had no positive effects on internet financial reporting. This result shows that companies in Indonesia do not relies on profitability when they disseminate financial information on their official web sites because the company performance does not affect society to legitimise that the internet is the medium that they use to view financial information.Keywords: financial report, internet, profitability